Impact of Motivation, Discipline, Job Satisfaction on Female Lecturer Performance at PH University - Meilani, Yohana F Cahaya Palupi; Bernarto, Innocentius; Berlianto, Margaretha Pink (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
This study intended to determine the impact of motivation, discipline, job satisfaction to performance of women lecturers of PH private university. The background of this study because women lecturers who have motivation, discipline, job satisfaction is expected to show their best performance. The study was conducted with quantitative methods, using questionnaires with five Likert scales distributed to 100 women lecturer from PH private university. Respondents had worked for at least two years as a permanent employee. This study used convenience random sampling and SEM PLS for data processing purpose. The results showed that motivation, discipline, job satisfaction have a positive effect on the performance of women lecturer PH university. The research is expected to provide input for the university to manage performance through motivation, discipline, job satisfaction of women lecturer